A study of haematological profile of malaria in a tertiary care centre of western Uttar Pradesh, India - Prasad, P. L.; Rai, Preeti Lata; Hussain, Mohd. Shoaib (International Journal of Contemporary Pediatrics, 2018)
Background: Malaria is a major health problem in tropics with a high morbidity and mortality. Malaria causes wide spectrum of manifestation both clinical as well as hematological. A variety of haematological alterations like progressively increasing anaemia, thrombocytopenia, leucocytosis or leukopenia and rarely disseminated intravascular coagulopathy (DIC) have been reported in malaria. Though clinical manifestation has been widely studied but there is paucity of work in hematological abnormality. Methods: The hospital based observational study was conducted in the Department of Paediatrics, Shri Rammurti Smarak Insitute of Medical Sciences (SRMSIMS), Bareilly. Ninety-eight cases were positive for malaria by peripheral smear or by rapid diagnostic test for malaria or by both. Results: In the present study, prevalence of malaria found to be (11.6 %). Out of 98 cases, 60 were males, majority of cases belonged to 9-12 years of age, followed by 4-8 years of age. Male:Female ratio is 1.57:1. There was neutrophilic predominance and low monocyte count in cases positive for plasmodium falciparum malaria. All the patients had microcytic hypochromic anemia as per mean of MCV. In haematological profiles of malaria neutrophil and monocyte showed statistically significant variations (P value ≤0.001) Conclusions: Anemia is the most common hematological abnormality. There was neutrophilic predominance and low monocyte count in cases positive for malaria which is highly significant. All the patients had microcytic hypochromic anemia as per mean of MCV. Profound thrombocytopenia is very common in malaria.